Reproductive biology of Nemipterus japonicus (Bloch, 1791) in the trawl grounds along the north-east coast of India - Rao, M. V. Hanumantha; Ghosh, Shubhadeep; Sreeramulu, K.; Mahesh, V. U.; Kumar, M. Satish; Muktha, M. (Indian Journal of Fisheries, 2018)
The reproductive biology of Nemipterus japonicus along the north-east coast of India was studied during 2012 – 2015 from the trawl landings. Adults dominated the landings. Significant contribution by females was observed in most months of the year. Size at first maturity was 15.1 cm. Peak spawning season was during August to February and September to March in the northern and southern regions, as evident in the proportion of mature females and GSI. Maturity and GSI was found to be correlated with SST. Fecundity increased with length and weight and varied from 13176 to 130798. Ova diameter distribution indicated it to be a multiple/batch spawner.